AN IMPLEMENTATION OF DESIGN TRACKING SYSTEM RESULTS USING HYBRID TRACKING SYSTEM (HTS) - Stevani Rika Natalia M; Muhammad Fahreza; Hermansyah Alam (Jurnal Scientia, 2023)
Orbital perturbation refers to the phenomenon where a satellite's orbit undergoes changes due to external influences like variations in Earth's gravitational field, gravitational interactions with the Moon, impacts from meteoroids or other objects, and the pressure exerted by solar radiation. To address these changes and maintain their intended orbits, satellites utilize small onboard thrusters. These thrusters are fired in specific directions to make course corrections, but this action consumes the fuel that the satellite carries from Earth. Over the past three decades, communication satellites have played a crucial role in global communication. In the 1960s, their primary mission was to enable point-to-point transmissions between continents. They achieved this by being positioned in geostationary orbits, which are located just above the equator and allow them to constantly observe approximately one third of the Earth's surface.